Endoscopic ultrasound and fine-needle aspiration for the detection of residual nodal disease after neoadjuvant chemoradiotherapy for esophageal cancer - van der Bogt, Ruben D.; van der Wilk, Berend J.; Poley, Jan-Werner; Krishnadath, Kausilia K.; Schoon, Erik J.; Oostenbrug, Liekele E.; Siersema, Peter D.; Vleggaar, Frank P.; Bruno, Marco J.; Biermann, Katharina; van Lanschot, J. Jan B.; Spaander, Manon C. W. (Endoscopy, 2020)
Background Endoscopic ultrasound (EUS) and fine-needle aspiration (FNA) are potential tools for the detection of residual disease after neoadjuvant chemoradiotherapy (nCRT) for esophageal cancer. This study investigated yield of EUS and FNA for detection of malignant lymph nodes (LNs) after nCRT.Methods This was a post hoc analysis of the preSANO trial. EUS was performed 10 – 12 weeks after nCRT. 18F-fluorodeoxyglucose positron emission tomography – computed tomography (18F-FDG PET-CT) was used to guide targeting of suspicious LNs. Consecutive FNA sampling was performed for suspicious LNs identified on EUS and/or PET-CT. EUS nodal staging was compared with histopathological examination of the resection specimen. The primary outcome was the proportion of correctly identified patients with malignant LNs by radial EUS.Results 101 consecutive patients were included: 79 patients had no malignant LNs, of whom 62 were classified correctly by EUS (specificity 78 %); 22 patients had malignant LNs, of whom 11 were identified (sensitivity 50 %). Six of these patients had ≥ 1 suspicious LN not fulfilling EUS criteria (round, hypoechogenic, > 5 mm). Malignant LNs in falsely negative patients were predominantly located at distal LN stations. Specificity and sensitivity of conclusive FNA outcomes were 100 % (7/7) and 75 % (3/4), respectively. FNA outcome was uncertain in eight patients, half of whom appeared to have malignant LNs.Conclusions EUS only detected 50 % of patients with malignant LNs 10 – 12 weeks after nCRT. To optimize sensitivity and minimize the risk of missing residual disease, FNA of LNs should be performed even in cases of low endosonographic suspicion.